Response to “Digital Health Technology & Cancer Care: Conceptual Framework Leading Comprehensive Fruitfulness” [Letter] - Arjanto P (Journal of Healthcare Leadership)
Paul Arjanto Department of Educational Management, Pattimura University, Ambon, IndonesiaCorrespondence: Paul Arjanto, Department of Educational Management, Pattimura University, Ambon, Jl. Ir. Putuhena, Ambon, Maluku, Indonesia, Email paul.arjanto@lecturer.unpatti.ac.id